EFEK PEMUASAAN PADA MASA DARA TERHADAP POLA PRODUKSI TELUR DAN DISTRIBUSI WAKTU OVIPOSISI PADA BURUNG PUYUH - Zurahmah, Nani (Fakultas Peternakan Universitas Papua, 2010)
The research is aimed to investigate the effect of fasting at grower period (3 to 6 week of age) on pattern of egg production and distribution of oviposition time in Japanese quail. Three hundreds and forty female of Japanese quails at 3 week of age were used in this research. The treatments were (1) without fasting or control, (2) skip-a-day fasting, (3) nighttime fasting: 18.00 p.m to 06.00 a.m.; and (4) daytime fasting: 06.00 a.m to 18.00 p.m. Data collected were age of the onset of laying (sexual maturity) until 12 weeks of age. The results showed that (1) the peak of egg production of control group was faster (10 weeks of age) and higher (89,3%) than the quails of groups fasting at grower period, but the peak of egg production was maintained longger than control group; (2) there was a fact that the egg production compensation was happened in fasting groups at grower period; (2) in quails group of daytime fasting at was grower period the distribution of oviposition time was relative smoother between periode observed: 12.00 – 18.00 p.m., 18.00 – 24.00 p.m. and 00.00 – 06.00 a.m., than other treatments.